Frequency of intestinal microeukaryotes in patients undergoing screening colonoscopy for colorectal cancer (2022)
ABSTRACT: Background and aims: Blastocystis sp. is one of the most common parasites infecting the human gut. According to IARC, protist species are not carcinogenic to humans. However, Blastocystis sp. has been associated with colon affections including colorectal cancer (CRC). This ongoing study investigates potential associations among Blastocystis sp. and other intestinal protists and a higher risk of developing CRC. Methods: Stool samples were collected from patients undergoing screening colonoscopy for CRC in two hospitals in Medellín, Colombia. The presence of microeukaryotic parasites was investigated by conventional (formalin-ether concentration technique, microscopic examination including Ziehl-Neelsen staining) and molecular (PCR and Sanger sequencing) methods. Results: A total of 80 patients (47 with normal colonoscopy, 5 with polyps, and 28 with a CRC diagnosis) were included in the study. Blastocystis sp. was the most prevalent enteric protist found (30%, 24/80), followed by Giardia duodenalis (2.5%, 2/80) and commensal amoebas (6.3%, 5/80). Within Blastocystis, the sub-type ST3 allele 34 was the most frequently found in the surveyed clinical population (54%, 13/24). ST3 allele 34 was more prevalently found in CRC patients (n=7) compared to those with polyps (n=2) or normal colonoscopy (n=4). Conclusions: Pathogenicity of Blastocystis remains disputable, but preliminary results from this study suggests that Blastocystis ST3 may enhance CRC development.